Chemical and energetic characterization of eucalyptus chips as a small-scale biomass power plant at mai-chew particle board factory site - Teklay Gebremariam , Limat; Gebregerges Gebreegziabher , Tesfaldet; Belete, Fentahun Abebaw (International Journal of Engineering and Technology, 2024)
Biomass has emerged as a renewable energy source with a high potential to contribute to the energy needs of both developed and developing countries. This study was aimed at analyzing the Ultimate, proximate, and heating value of the white eucalyptus biomass waste was characterized and is high quality for bioenergy purposes. From the triplet experimental results of the on proximate analysis of the biomass were 81.711, 0.98, 3.099, and 14.21% for volatile content, ash content, moisture content, and volatile matter respectively. In addition, the ultimate analyses of the eucalyptus chips were 49.7, 6.08, 0.24, 43.913, and 0.067% for Carbone, hydrogen, nitrogen, oxygen, and sulfur content respectively. Finally, the lower heating value (LHV) and higher heating value (HHV) were 18,675.49 and 19,992.07283 KJ/Kg respectively.